Mendidik Lewat Literasi untuk Pendidikan Berkualitas - I Made Ngurah Suragangga (Jurnal Penjaminan Mutu, 2017)
Culturally Indonesian society does not have a high literacy culture. The results of the research program for International Student Assessment PISA) mentions, cultural literacy rate of Indonesian society the second worst from 65 countries that are examined in the world. Indonesia occupies the sequence to 64 from 65 countries. While Vietnam thus occupy the century . On the same research, PISA also put the position of the read the students of Indonesia in order to 57 from 65 countries that are examined. Indonesia has experienced an emergency literacy rate. The culture of literacy must be forced and accustomed to become the culture. This literacy culture will affect the quality of education and human resources that are produced. The problem of the low literacy rate, especially in the education line, not only the responsibility of the government. Needed a serious and sustainable synergy, both in the family, schools, universities, even the community to realize that literacy become main culture.